Analysis of English Abbreviations Found in The Jakarta Post's Articles Published in January 2021 - Ira Dwi Rahmawati; Ismawati Ike Nugraeni; Sri Widodo (Scripta : English Department Journal, 2022)
This research deals with the types and meaning of abbreviation found in the Jakarta Post’s articles published in January 2021 and its application in teaching vocabulary. The aims of this research are to identify the classifications of the type abbreviation found in the Jakarta Post’s articles and to describe the application of abbreviation found in the Jakarta Post’s articles in teaching vocabulary. This research is a descriptive qualitative research. In this research, the data source is taken from the Jakarta Post’s articles. In analyzing the data, the researcher was identified the abbreviation, classifying the data into types of abbreviation, giving code of each data, counting the data, applied the result of the analysis to teach vocabulary, and draw conclusion and suggestion. The result this study shows that there are 25 initialisms which contains 45%, 8 of unit abbreviation (15%), 1 of unit of measurement (2%), 5 of acronym (9%), 16 of contractions (29%), 0 suspensions (0%). This research can be applied in teaching vocabulary for the twelfth-grade students of senior high school.